Right to information: Issues of administrative efficiency, public accountability and good governance in India - Shamshad, Ahmad (2009)
The Right to Information Act is truly a historic and a comprehensive legislation that would confer statutory rights on citizens for seeking information from public authorities. The Act is expected to usher in a new era of governance and promote more transparency and accountability. Concerns, however remain about its effective implementation and operationalisation. It is implicit in the Constitution of India, which establishes a representative democracy with alienable rights for the citizens of the country, which have been reinforced time and again by judiciary. RTI in India has significantly sought to expand democratic space and empower the citizens to exercise more control on the corrupt practices under the power of the state. it is as crucial as freedom of expression in any democracy. It is only through information and resultant expressions that people can influence the government of the people, for the people and by the people. - Reproduced.
Keywords: Public administration; Good governance; Accountability; Right to information